Revitalising and Renovating the Visitor Experience in the Historic Piazza San Marco; Based on the Installation Project Generated by Midjourney AI - Mousavi, Seyed Mohammad Amin Mostafavi; Dinçer1, Ebru Erdönmez (İstanbul Üniversitesi, 2024)
The historic San Marco Square, a UNESCO World Heritage Site and Venetian architectural symbol, will encounter a challenge in balancing its historical relevance with the evolving demands of a modern public space. This article investigates the potential of artificial intelligence (AI), specifically Midjourney AI, to revitalise the Square’s visitor experience while maintaining its distinct identity. By studying the Square’s spatial features and "Quality of Place" specifications, this paper recommends the installation of AI-powered installations to enhance comfort and social interaction. During the period which these installations are exposed to customers and visitors, the goal is to preserve the historical context while also inspiring people with a renewed sense of amazement and participation. Based on research in urban planning and cultural heritage management, the study claims that AI technology could be an effective tool for improving public areas while maintaining their historical integrity. This approach is consistent with the rising emphasis on human-centred design in public places, which values diversity, accessibility, and an impression of community.
Keywords: Architecture (Other); Mimarlık (Diğer)